2020
DOI: 10.1021/acssynbio.0c00315
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Control of the BMP Signaling Pathway

Abstract: Bone morphogenetic proteins (BMPs) are members of the transforming growth factor β (TGFβ) superfamily and have crucial roles during development; including mesodermal patterning and specification of renal, hepatic, and skeletal tissues. In vitro developmental models currently rely upon costly and unreliable recombinant BMP proteins that do not enable dynamic or precise activation of the BMP signaling pathway. Here, we report the development of an optogenetic BMP signaling system (optoBMP)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…More recently, Wnt and BMP signaling pathways were identified as critical cues for cardiac organoid selforganization and chamber formation in 3D, in which CMs and endothelial cells were both formed in the same aggregates. 19,20 With the advent of optogenetic control of BMP signaling, 23 we may be able to precisely pattern the differentiation of CMs, endothelial cells and/or epicardial cells via optogenetics to achieve spatially-organized cardiac tissues/ organoids with high consistency and reproducibility. In the future, OptoWnt could be combined with 3D cell culture, orthogonal light control of other developmental signaling pathways, and advanced optical patterning techniques to achieve more physiologically relevant hPSC organoid models with intricate geometries and orthogonally controlled cell positions for studying human development and disease.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Wnt and BMP signaling pathways were identified as critical cues for cardiac organoid selforganization and chamber formation in 3D, in which CMs and endothelial cells were both formed in the same aggregates. 19,20 With the advent of optogenetic control of BMP signaling, 23 we may be able to precisely pattern the differentiation of CMs, endothelial cells and/or epicardial cells via optogenetics to achieve spatially-organized cardiac tissues/ organoids with high consistency and reproducibility. In the future, OptoWnt could be combined with 3D cell culture, orthogonal light control of other developmental signaling pathways, and advanced optical patterning techniques to achieve more physiologically relevant hPSC organoid models with intricate geometries and orthogonally controlled cell positions for studying human development and disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that other groups have recently shown that Smad1/5 activation can be induced in optogenetic BMP and TGFBR/ACVR signaling systems when BMPR1B/BMPR2 or TGFBR1/ ACVR1 proteins are anchored to the plasma membrane through an N-terminal myristoylation. [22,23] If TGFβ receptor internalization is not necessary for Smad2 activation, to what extent might it contribute to Smad2 signaling? It has been reported that chemical inhibition of endocytosis can impair TGFβ-induced Smad2 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Our optoWnt system involves fusion of the intracellular portion of the canonical Wnt co-receptor LRP6 to the PHR domain of Cry2 ( Figure 1D ), and we have reported optogenetic activation of Wnt signaling in both adult neural stem cells (NSCs; Bugaj et al, 2013 ) and human embryonic stem cells (hESCs; Repina et al, 2020 ). Other emerging and relevant morphogen signals to neurodevelopment include optoFGFR1(Kim et al, 2014 ), optoTGF (Li et al, 2018 ), optoBMP (Humphreys et al, 2020 ), and optoBrn2 (Sokolik et al, 2015 ), which have clear applications in modeling neurodevelopment and neurogenesis if translated to either pluripotent stem cells or adult neural stem cells.…”
Section: Optogenetics In Organismal Developmentmentioning
confidence: 99%